Alternate Day Fasting terhadap Berat Badan, dan Enzim Transaminase pada Tikus Putih Galur Sprague Dawley - Harahap, Huntari (LPPM Universitas Jambi, 2024)
ABSTRACT Background Obesity is a global epidemic problem that can increase the risk of metabolic syndrome and insulin resistance. Modification of diet and moderate exercise can control metabolism. Alternate Day Fasting is one of the intermittent fasting diet modifications where the day alternates between normal and fasting diets. When fasting can consume food substances 20-25% of total energy. Aim this research objective was to determine the effect of the Alternate Day Fasting diet on body weight, and liver function. Method this research is an experimental study on male Sprague Dawley rats aged 2-3 months, weighing 150-250 grams, and no anatomical abnormalities, which are divided into 2 groups, namely control (n = 10) and Alternate Day Fasting (n = 10). Results the Alternate Day Fasting can reduce body weight (mean = 197.5) compared to controls (mean = 253.6). There was no difference in blood glucose (Mann Whitney; p> 0.05), Serum Glutamic Oxaloacetate Transaminase (Mann Whitney; p> 0.05), Serum Glutamic Pyruvic Transaminase (Mann Whitney; p> 0.05) between the control group and the Alternate Day Fasting diet. Conclusion Alternate Day Fasting Diet can lose weight, and does not result in an increase in Serum Glutamic Oxaloacetic Transaminase and Serum Glutamic Pyruvic Transaminase. Keywords: Obesity, Alternate_Day_Fasting, body_weight, SGOT, SGPT